Performa Teknis Kapal Handline Anita Jaya X di Pelabuhan Perikanan Samudera Cilacap: Technical Performance of Handline Vessel Anita Jaya X at Samudera Cilacap Fishery Port - Yuwandana, Dwi Putra; Amalia, Farah Nur; Bangun, Tri Nanda Citra (Universitas Sam Ratulangi, 2025)
The fishing industry is a vital sector for the global economy and food security because this industry plays a role in providing food and economic income for business actors. However, the fishing industry also often faces challenges such as competition to obtain supplies of fresh fish raw materials. The decline in the quality of caught fish is also influenced by handling that does not comply with standards or inadequate storage conditions. The loading capacity of a ship is influenced by the value of the ship's displacement, the ship's dead weight, and the weight of the empty ship. Therefore, this research aims to estimate the value displacement, empty ship weight (Light Weight Ton/LWT), ship dead weight (Dead Weight Tonnage/DWT), and the maximum amount of catch that can be loaded on the ship. Collecting research data by taking ship measurements and interviews. The sampling technique is carried out randomly accidental sampling. The research results show that the Anita Jaya X ship has value displacement amounting to 72.02 tons, empty ship weight (Light Weight Ton/LWT) of 12.15 tons, and ship dead weight (Dead Weight Tonnage/DWT) of 59.87 tons. Therefore, it can be concluded that to avoid a decrease in the quality of caught fish due to mismatches in the loading capacity and hold of caught fish then the Anita Jaya X can load up to 53.71 tons of fish.